Rethinking productive development sound policies and institutions for economic transformation - Crespi, Gustavo; Fernandez-Arias, Eduardo (Palgrave Macmillan, 2014)
"Rethinking Industrial Policy systematically analyzes policies in key areas such as innovation, new firms, firm networks, financing, human capital, and internationalization. The authors provide an in-depth look at specific policies and institutions that illustrate the do's and don'ts emerging from regional and international experience on the basis of the analytic tests, and they review new approaches to gauging the opportunities countries have for beneficial productive transformation into new and better products. The book discusses how these analyses are useful to inform policy to stimulate and guide productive transformation"-- Provided by publisher.